Leveraging Applications of Formal Methods, Verification and Validation Third International Symposium, ISoLA 2008, Porto Sani, Greece, October 13-15, 2008, Proceedings - Margaria, Tiziana.; Margaria, Tiziana.; Steffen, Bernhard.; Steffen, Bernhard. (Communications in Computer and Information Science,, 2008)
This book constitutes the thoroughly refereed proceedings of the Third International Symposium on Leveraging Applications of Formal Methods, Verification and Validation, held in Porto Sani, Greece, in October 2008 The 68 revised full papers presented together with 2 invited talks and 1 keynote speech were carefully selected from numerous submissions. The topics covered are tools and applications in industrial software quality control; an introduction of multi-core systems in automotive applications; model-driven SOA; applications of formal approaches to service-oriented computing; trustworthy computing: theories, methods, tools and experience in China and South East Asia; non-functional requirements in embedded systems; processes, methods and tools for developing educational modules to support teaching and technology transfer; ubiquitous and context aware systems; formal methods for analysing and verifying very large systems; tools for service-oriented discovery of knowledge; tackling the challenges of software development process for SMEs with rigorous support and open source.